Soil Science Emerging Technologies, Global Perspectives and Applications - Aide, Michael; Braden, Indi (IntechOpen, 2022)
Soil Science - Emerging Technologies, Global Perspectives and Applications describes recent research that illustrates the universal importance of understanding soil and soil's relationship to environmental stewardship and food security. Research supporting emerging technologies provides abilities to discern key soil attributes that influence soil behavior and development, understand soil biology to create sustainable land management, and sequester carbon to partially negate climate change. Soil science is an interdisciplinary field of inquiry that must consider resource allocation and social needs to foster a culture that protects and secures not only soil health but also water and air quality. Chapters in this book reflect the diversity of modern thinking within the discipline of soil science, but collectively illustrate that global sustainability of food, the environment, and biological diversity are critical to future generations.